A Reward System for Improving Teacher Performance in State Madrasah Aliyah (Islamic Senior High Schools) Jambi Province - Achmad Fadlan; Ahmad Syukri; Kasful Anwar (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2025)
This study aims to analyze the reward system in improving the performance of educators at State Islamic Senior High Schools (Madrasah Aliyah) in Jambi Province. The research focuses on the reward mechanism, its implementation, and the factors that determine its effectiveness in improving educator performance. This study uses a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation. The research locations include three madrasas: MAN 1 Tanjung Jabung Barat, MAN 1 Kota Jambi, and MAN 1 Merangin. The results show that the implemented reward system includes financial rewards (such as incentives and allowances) and non-financial rewards (such as certificates, training, and job promotions). Rewards have been shown to play an important role in improving educator motivation, discipline, loyalty, and performance. However, the implementation of the reward system has not been optimal due to several obstacles, such as budget constraints, lack of transparency in assessments, and the incompatibility of the types of rewards with the needs of educators. On the other hand, madrasas that implement the reward system appropriately and fairly show an increase in the quality of educator work, marked by increased participation, work performance, and professional responsibility. This study concludes that an effective reward system is one that has clear criteria, is transparent, and responsive to the needs of educators. Recommendations are directed to madrasah principals and the Ministry of Religious Affairs to build a strong culture of appreciation and allocate an adequate reward budget to improve the quality of education in madrasahs.